The Analysis of Sarcasm in Comedy Film Entitled “The Dictator” - Nugroho, Muhammad Aprianto Budie; Suryana, Yayan; Putra, Ade Septa Ganda (Universitas Nurul Jadid, 2025)
This research aims to analyze sarcasm in a comedy film entitled The Dictator. The subject of this research is dialogue containing sarcasm in the movie. The research focuses on the analysis of sarcasm in a comedy film entitled The Dictator and classifying them into types of sarcasm by explaining the meaning of each word in the dialogue. This study deals with the use of sarcastic comedy analysis by theory: camp (2011). The objective is to find out the types and meanings of sarcastic comedy shown in a film entitled The Dictator. Qualitative method is used in this research, with case study as the design of this research, because the research intended to analyze sarcasm in a comedy film entitled The Dictator. In analyzing of film entitled The Dictator, there are two data sources for analysis namely: the film video and The Dictator movie script. The result of data analysis showed that there were 66 sarcastic expressions spoken by the characters entitled The Dictator film. In this research, those data are analyzed and classified into different types of sarcasm. There are propositional, illocutionary, “ike-prefixed, and lexical sarcasm. This film is mostly about how to satire the style of Muammar Khadafi the Dictator of Libya. They also satirized the American government and the country of Israel about their nuclear arsenals, and the government of America considered to be hypocritical because the American government admitted defending human rights but they are also supporting dictatorial leadership in Middle East.